Impact of weather constraint on tomato leaf miner Tuta absoluta (Meyrick) (Lepidoptera: gelechiidae) phenology in field and greenhouse investigations - Taha, Hanan Salah El-Din (International Research Journal of Insect Sciences, 2025)
In the global climate, a higher temperature increase than in recent decades is expected, especially affecting insects susceptible to the hottest summer events, such as the tomato leaf miner Tuta absoluta (Meyrick), which is responsible for severe tomato yield losses. Samples were taken from fields and greenhouses. Larvae collected were kept in the laboratory at various constant temperatures to investigate the effects on development and mortality of the immature stages and to determine the thermal units required for development in relation to the minimum and maximum daily temperatures (DDs) over several months. The Daily Degree Units (DDU) results for the generation of T. absoluta per year were 404.46, 313.67, 404.46, 374.13, and 441.79 for Menufia, Sharkia, Kalubia, Dakahlia, and Giza, respectively. Temperature correlation values for the same locations ranged from 0.789, 0.78, 0.594, 0.736, and 0.72. The relationship with rainfall was positive and significant. Non-significant values were found for mean temperature, relative humidity, and bright sunshine hours. This work aids in the prediction of generation times, the number of generations per year, and the development rate of each generation at different times and locations, both for current and future years.